Evaluating Factors Influencing Technical Efficiency and Milk Yield in Dairy Farms: Evidence from the Gaziantep Region, Türkiye - Tosun, Hİ (Journal of the Hellenic Veterinary Medical Society, 2025)
The dairy industry is a vital component of Türkiye’s agricultural sector, contributing significantly to the national economy. This study examines the technical efficiency of dairy farms in the Gaziantep region, a key dairy-producing area in Türkiye, to identify factors influencing milk yield and technical efficiency. Data were collected from 791 dairy farms using stratified random sampling. The study employed the Stochastic Frontier Analysis to estimate efficiency scores, focusing on variables such as feed intake, udder health, and management practices. Technical efficiency scores ranged between 0.65 and 0.99, with an average of 0.95. The coefficients of the variables explaining inefficiency were as expected. By addressing these inefficiencies, milk yield in the region could potentially increase by 5.00% with the same inputs, which would improve overall efficiency. The analysis revealed that udder health management practices, including pre- and post-dipping, the use of headlocks after milking, and vaccination programs, significantly impact TE and milk yield (t-values: -2.584, -1.681, and -2.909, respectively). The findings underscore the importance of proper management practices in enhancing the efficiency and productivity of dairy farms. This study provides valuable insights for policymakers, farmers, and researchers aiming to improve dairy farm efficiency and sustainability.